Proceso de atención de enfermería en paciente de 28 años con 29 semanas de embarazo y diabetes gestacional. - Valle Monserrate, Erick Rolando (2022)
Gestational diabetes is considered as the inability to tolerate carbohydrates, resulting in hyperglycemia that is recognized during pregnancy. Its prevalence is between 2-5% and it is related to type 2 diabetes mellitus. This condition has a negative impact on the pregnant woman and the new being. This clinical case study focuses on a 28-year-old patient with 29 weeks of pregnancy diagnosed with gestational diabetes, with no history of obesity, sedentary lifestyle and smoking who was admitted to the obstetric emergency area for presenting: Polydipsia, polyuria, asthenia and vomiting. Physical examination revealed moderate dehydration; Laboratory tests show hyperglycemia. Through the evaluation of the functional patterns of Marjory Gordon, the following stands out: Alteration of pattern 2: nutritional-metabolic, pattern 3: elimination and pattern 10: adaptation and tolerance to stress. Considering the data obtained from the initial assessment, the nursing diagnoses established in the NANDA were made: risk of unstable blood glucose level and risk of fluid volume imbalance. Once the diagnoses were raised, goals proposed by the NOC were established, focused on improving the glycemic level and water balance. The interventions dictated by the NIC focus on the management of the level of hyperglycemia and fluid/electrolyte management. The clinical management of the patient was carried out effectively, with a favorable evolution evidenced in the follow-up. The goals were met indicating the correct approach of the interventions proposed in the nursing care process.